1994
DOI: 10.1111/j.1600-0676.1994.tb00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic change in portal fibroblasts in biliary fibrosis

Abstract: Portal fibroblasts have been considered responsible for biliary fibrosis. Since lipocytes show differentiation toward myofibroblast‐like cells in hepatic fibrogenesis, we studied whether similar differentiation of portal fibroblasts could be observed in biliary fibrosis. We examined rat livers after bile duct ligation by double immunofluorescent staining of α‐smooth‐muscle actin (α‐smA) and desmin and also by electronmicroscopy. In the portal tract of normal livers, α‐smA‐positive cells were noted only in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Although the role of aPFs in the development of portal fibrosis has been discussed (42, 61), our study is the first to our knowledge to quantify the myofibroblast populations over a time course. Consistent with previous studies (62,63), we demonstrate that aPFs play an important role at early stages of BDL-induced liver fibrosis (13) by contributing >70% of myofibroblasts. Moreover, even at later stages (BDL, 17-20 d), aPFs contribute ∼50% of myofibroblasts and exhibit a more activated phenotype than aHSCs.…”
Section: Ahscs and Apfs Contribute Differently To Liver Fibrosis Of Dsupporting
confidence: 93%
“…Although the role of aPFs in the development of portal fibrosis has been discussed (42, 61), our study is the first to our knowledge to quantify the myofibroblast populations over a time course. Consistent with previous studies (62,63), we demonstrate that aPFs play an important role at early stages of BDL-induced liver fibrosis (13) by contributing >70% of myofibroblasts. Moreover, even at later stages (BDL, 17-20 d), aPFs contribute ∼50% of myofibroblasts and exhibit a more activated phenotype than aHSCs.…”
Section: Ahscs and Apfs Contribute Differently To Liver Fibrosis Of Dsupporting
confidence: 93%
“…Although hepatic stellate cells are well established as the predominant source of ECM in parenchymal fibrosis, portal mesenchymal cells play an important role in biliary fibrosis 2831 . In agreement with these reports, we found that, while there were many αSMA-expressing myofibroblasts in the portal region following bile duct ligation (Supplemental Figure 10A), there were few hepatic stellate cells (as determined by staining for desmin, red) (Supplemental Figure 10B).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it enhances motility in hepatic stellate cells but not portal fibroblasts, a phenotype that specifically requires EIIIA and integrin α 9 β 1 . Male EIIIA−/− mice are protected from thioacetamide-induced fibrosis, which primarily affects the sinusoids, but not from bile duct ligation-induced fibrosis, which affects the portal area and may depend more on portal fibroblasts 2831 . The data provide proof of concept that subtle changes in the ECM can have large effects on myofibroblast behavior and liver fibrosis, and they highlight a previously unappreciated function of EIIIA+ cFN in promoting stellate cell motility rather than myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…11 There is evidence, in particular, to indicate that mesenchymal cells in the portal tract, which include fibroblasts located around bile ducts 11 give rise to myofibroblasts in biliary-type liver fibrosis. [12][13][14][15][16][17] As the portal area is a prominent location of fibrosis development not only in biliary diseases, but in virtually all types of chronic liver diseases, including viral and alcohol-related diseases, 18,19 the implication of portal mesenchymal cells in the formation of liver fibrosis may be more important than what has been generally assumed. However, no marker(s) has been identified that allows, so far, to fully discriminate these cells from HSCs at the stage of myofibroblasts, 14,[20][21][22][23] and to what extent these cells compared with HSCs may actually contribute to liver fibrogenesis is at present largely unknown.…”
mentioning
confidence: 97%